2019
DOI: 10.1111/jpn.13207
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the source and dosage of dietary Cu on redox status in rat tissues

Abstract: The aim of this experiment was to investigate whether the amount of Cu added to the diet of rats can be reduced without adversely affecting the antioxidant status of tissues and growth, and whether copper nanoparticles can be used for this purpose. For four weeks, four experimental groups of rats were fed diets with two dosages of added Cu (standard—6.5 or 3.25 mg/kg) in two forms (standard—CuCO3 or copper nanoparticles). Replacing the CuCO3 supplement with CuNPs resulted in a decreased lung weight and an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Nevertheless, others indicated that the application of CuNPs in animal nutrition, apart from the benefits, may carry a significant risk due to the potential toxicity of CuNPs [ 11 , 13 , 14 , 15 , 16 , 17 ]. Our results are partly consistent with these reports, as we proved an increase in Cu accumulation in the brain, kidneys and lungs, as well as an intensification of lipid peroxidation or impairment of antioxidant defence [ 18 ]. Due to such a broad physiological effect of CuNPs in the body, indicating positive and negative effects, it may be important to regulate the area of their reactivity.…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…Nevertheless, others indicated that the application of CuNPs in animal nutrition, apart from the benefits, may carry a significant risk due to the potential toxicity of CuNPs [ 11 , 13 , 14 , 15 , 16 , 17 ]. Our results are partly consistent with these reports, as we proved an increase in Cu accumulation in the brain, kidneys and lungs, as well as an intensification of lipid peroxidation or impairment of antioxidant defence [ 18 ]. Due to such a broad physiological effect of CuNPs in the body, indicating positive and negative effects, it may be important to regulate the area of their reactivity.…”
Section: Introductionsupporting
confidence: 93%
“…Copper nanoparticles (99.9% purity powder, 40–60 nm size, 12 m 2 /g specific surface area (SSA), spherical morphology, 0.19 g/cm 3 bulk density, 8.9 g/cm 3 true density) were obtained from Sky Spring Nanomaterials Inc. (Houston, TX, USA). CuNPs with the same properties were also used in our previous studies [ 11 , 12 , 13 , 18 , 31 ]. α-Cellulose was used as a control dietary fibre source (Sigma, Poznań, Poland).…”
Section: Methodsmentioning
confidence: 99%
“…However, metal NPs carry a possible risk that outstate the benefits of ionic forms due to the potential toxicity of NPs themselves. Only a few recent studies are partly consistent with safety reports, in contrast to many others which point towards the intensification of lipid peroxidation and impairment of antioxidant defense mechanisms [ 4 ].…”
Section: Introductionmentioning
confidence: 55%
“…accumulated in the kidneys of chickens fed diets containing potassium chromate. In our previous study on Wistar rats subjected to dietary treatments with nano-copper, those small nanoparticles were accumulated in the brain tissue, while such an effect was not observed in the case of CuCO 3 added to a mineral mixture [Ognik et al, 2020]. An interesting observation was made by Staniek [2019] in female rats fed diets containing low (1 mg/kg), medium (50 mg/kg) and high (500 mg/kg) contents of chromium(III) without (recommended level 45 mg/kg) or with dietary excess (180 mg/kg) of iron.…”
Section: Resultsmentioning
confidence: 84%